2013
DOI: 10.1161/circheartfailure.112.000098
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Left Ventricular Mechanics in Pulmonary Arterial Hypertension

Abstract: P ulmonary arterial hypertension (PAH) is characterized by pulmonary vascular remodeling, right heart failure, and reduced survival.1 Both symptoms and extent of right heart failure predict mortality. [2][3][4] Measures of RV filling pressure and systolic function have been shown to correlate with clinical disease progression and survival. 5-8 Clinical Perspective on p 755Right ventricular (RV) contraction is a complex process related to a variety of actions, the predominant being longitudinal motion because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
95
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 50 publications
13
95
0
2
Order By: Relevance
“…Recently, a study on echocardiography in adults with PAH identified reduced systolic strain of the LV-free wall as a predictor of early mortality. 48 The observed correlation of echocardiography with both disease severity and outcome is supported by our finding, in a subgroup, that the echo variables were also associated with hemodynamic measures. The relationship of echocardiographic characterization of the RV with hemodynamics was recently further supported by Di Maria et al, 10 who showed TAPSE and RV-fractional-area-change to be associated with RV-stroke-work, which is a hemodynamic measure integrating information on RV performance and ventricular-vascular coupling.…”
Section: Discussionsupporting
confidence: 63%
“…Recently, a study on echocardiography in adults with PAH identified reduced systolic strain of the LV-free wall as a predictor of early mortality. 48 The observed correlation of echocardiography with both disease severity and outcome is supported by our finding, in a subgroup, that the echo variables were also associated with hemodynamic measures. The relationship of echocardiographic characterization of the RV with hemodynamics was recently further supported by Di Maria et al, 10 who showed TAPSE and RV-fractional-area-change to be associated with RV-stroke-work, which is a hemodynamic measure integrating information on RV performance and ventricular-vascular coupling.…”
Section: Discussionsupporting
confidence: 63%
“…Postoperative improvement of myocardial function due to a prominent decrease in RV load and pressure may be evidence of that mechanism. Previous studies have shown that LV dysfunction is associated with increased mortality and morbidity in patients with PH [24]. In our study, we demonstrated that conventional LV dimensions significantly increased after PTE, although there was no change in LVEF.…”
Section: Discussionsupporting
confidence: 53%
“…Th is may be a result of reduced LV preload, but previous studies have also demonstrated by LV strain imaging that LV contractility and LV torsion are impaired in patients with PAH. 29,31 Furthermore, according to the LV pressure-volume relationship, an increased LVESV is associated with impaired LV contractility.…”
Section: Discussionmentioning
confidence: 99%